The Effectiveness of Teaching Applied Transference Focused Psychotherapy on the Attitudes and Technical Confidence of Psychiatry Trainees in Malaysia, on the Management of Patients with Personality Disorder. - Muhammad Nur Arif Abdul Rassip; Salina Mohamed; Salmi Razali; Dinah Rasidi; Tennyson Lee (BJPsych Open, 2025)
Aims: Psychiatric trainees are often the “first responders” to manage patients with personality disorders but receive little specific training in this. Transference Focused Psychotherapy (TFP) is a manualized evidence-based treatment for severe personality disorders based on a psychodynamic approach that focuses on object relations theory. There is an expanding experience in applying TFP in different psychiatric settings. While there is evidence of effective training of applied TFP in the UK, Europe, South Africa and India, TFP training in Malaysia is a relatively new concept.